A study to clarify whether sunn pest (Eurygaster integriceps) increases amylase activity in wheat - Halef Dizlek; Mehmet Sertaç Özer (Heliyon, 2024)
There is uncertainty as to whether amylase is injected into wheat kernels by the sunn pest (SP). There are conflicting results in the literature as to whether the amylolytic activity (AA) of insect-damaged wheat is increased. Therefore, the research question of this study is whether amylase is injected into wheat kernels by SP. Two bread wheat cultivars with different levels of SP-damage were used (first year Golia 2.35 % SP damaged kernel ratio [SPDR], second year Golia 3.92 % SPDR and Sagittario 7.8 % SPDR). Sound and SP-damaged wheat (SPDW) kernels were manually separated. In addition, SPDW kernels were divided into four categories according to their infection rates. The AA of these different wheats was determined by using AACC methods 22-05.01 and 56–81.04. In cultivar Golia, the α-amylase activity of the most damaged wheat (C4/4 WGWF) was 9.5 times higher than that of the undamaged wheat. The SP-damaged samples had a lower Falling Number (FN), i.e. higher AA, than the undamaged samples in both cultivars. The FN values of the flour samples prepared from the 100 % SPDW were reduced by up to 40 % compared to the undamaged samples. In conclusion, we clearly found increased amylase activity in SPDW. As the proportion of insect-damaged kernels in the wheat mass increased, the AA of the wheat and its flour also increased, as did the proteolytic activity. Because the AA in some wheats is insufficient for bread-making, SPDW can be blended to sound wheat varieties within certain limits to reduce or reset the use of amylase base additives and reduce bread costs.